Designing a Inventory Information System and Web-Based Transaction Recording Case Study at the Sinar Berkah Agung Building Store - Mulyanah Mulyanah; Ifan Junaedi; Anton Zulkarnain Sianipar (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
Sinar Berkah Agung Building Store is one of the lower-middle-class companies engaged in the sale of building materials, where the recording of stock of goods at the Sinar Berkah Agung building store is still done manually. This means that in terms of recording and processing data still using a piece of paper (paper based system) in handwriting which causes errors in recording data reports. Sales transactions are also still carried out manually on note recording which allows for recording errors to be lost. The recording and management of goods data that is still manual has many problems, such as errors in the recording process. With this problem, the time and energy spent will be greater. To solve this problem, the company needs an information system for recording inventory, sales transactions, and sales reports. With this system, it is possible to collect inventory data and process sales transactions simultaneously and programmatically, maintain data security and can produce a report desired by the company, so that if the data will be used at any time it is very easy to get it and does not take time. long time.